Unseen : unpublished black history from the New York Times Photo Archives - Swarns, Rachel L. (Black Dog & Leventhal Publishers, 2017)
Hundreds of stunning images from black history have long been buried in the New York Times archives. None of them were published by the Times--until now. Unseen uncovers these never-before published photographs and investigates the stories behind them.